1990
DOI: 10.1104/pp.93.2.822
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Dependence of the Apparent Km of Glutathione Reductases from Three Plant Species

Abstract: The thermal dependencies of the apparent Km of the glutathione reductases from spinach (Spinacia oleracea L.) corn (Zea mays L.), and cucumber (Cucumis sativus L.) were determined. The apparent Km of the enzymes were found to vary up to 9-fold between 12.5 and 450C. Values of the apparent Km in excess of 200% of the observed minimum are suggested to be detrimental to the normal function of the enzyme. We propose the term "thermal kinetic window" to describe to the range of temperatures over which the apparent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
31
1

Year Published

1991
1991
2013
2013

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 15 publications
3
31
1
Order By: Relevance
“…Using the criterion of 200% of the minimum K , for determining the TKW (Burke et al, 1988) resulted in a TKW encompassing temperatures from 23.5 to 39OC with a minimum apparent K, value at 32.5OC. These results differ from those reported previously for cucumber NADPH-glutathione reductase in that the range of temperatures delineating the TKW is from 23.5 to 39OC rather than from 35 to 41OC (Mahan et al, 1990). The upper limits of the TKW in the two studies are similar; however, the lower limits differ by more than 10°C.…”
Section: Tkw Determinationcontrasting
confidence: 57%
See 3 more Smart Citations
“…Using the criterion of 200% of the minimum K , for determining the TKW (Burke et al, 1988) resulted in a TKW encompassing temperatures from 23.5 to 39OC with a minimum apparent K, value at 32.5OC. These results differ from those reported previously for cucumber NADPH-glutathione reductase in that the range of temperatures delineating the TKW is from 23.5 to 39OC rather than from 35 to 41OC (Mahan et al, 1990). The upper limits of the TKW in the two studies are similar; however, the lower limits differ by more than 10°C.…”
Section: Tkw Determinationcontrasting
confidence: 57%
“…Because of the difference in TKW between that determined for NADH-hydroxypyruvate reductase in the present study and that reported previously for NADPHglutathione reductase (Mahan et al, 1990), we have used the fluorescence technique to further establish the bounds of the temperature optimum of cucumber.…”
Section: Fluorescence Analysesmentioning
confidence: 99%
See 2 more Smart Citations
“…These measures are used as indicators of metabolic efficiency. The TKWs have been identified for several crop species (1,2,4,5). These TKWs are narrower than plant temperatures experienced on a seasonal or daily basis (2).…”
mentioning
confidence: 99%